THE ROLE OF RELIGIOUS EDUCATION IN FORMING TOLERANT INDIVIDUALS - Sanaky, Hujair AH. (Universitas Islam Indonesia, 2017)
This article discusses the role of religious education in shaping and developing the attitude of tolerance in the context of Indonesia’s diversity of race, ethnicity, culture, and religion. It argues that in a multi-religious society such as Indonesia, education should provide an overview and moral ideals of religion contextually. Educational process thus requires a review of rigid and less humanist religious doctrines that have been held so far. The plurality of religions and beliefs are no longer understood as the potential for unrest, but the potential to implement their teachings for the sake of humanity. It further argues that education has an important role to play in fostering early attitude, not only in accepting the existence of other religions, but also in cooperating with those who have different beliefs or religions. This means that education should enable the growth of the brotherhood in unity, so people can jointly build the world a new which is more meaningful for all humanity. Educational design should accommodate pluralist and tolerant attitude. This requires learning materials and teachers’ attitudes which are tolerant and pluralist as well. Keywords: Religious Education, Diversity, Pluralism, Tolerance